Засоби масової комунікації як суб`єкт політичного процесу : символічний аспект. - Мамонтова, Е.В.; Мамонтова, Е.В.; Mamontov, E. (My University, 2011)
An attempt to expose symbolic nature of communication as the social phenomenon is carried out in the article. The speciﬁ c of postmodern tendency of symbolizing of the world of policy lights up through description of basic functions of facilities of mass communication.
Мамонтова Е.В. Засоби масової комунікації як суб`єкт політичного процесу : символічний аспект. / Е.В. мамонтова // Актуальні проблеми політики : Збірник наукових праць / Керівник авт. кол. С. В. Ківалов; відп. за вип. Л. І. Кормич. – Одеса: Фенікс, 2011. – Вип. 41. – С. 149 - 154 .
Keywords: Засоби інформації; Комунікації; Політичний процес; Засоби масової комунікації; Средства массовой комуникации; Политический процесс; Комуникации; Средства информации; media; COMMUNICATION; The political process; Media adverse communication